Mechanical properties of hydroxyapatite-magnesium orthosilicate composite / Jeffrey Chin Kong Leong - Jeffrey Chin , Kong Leon (2017)
Hydroxyapatite (HA) bioceramic has attracted a great deal of attention in the past two decades due to its similarity in terms of chemical structure to that of hard tissues. However, a major drawback of HA is the low fracture toughness (< 1 MPam1/2) exhibited by the ceramic. Magnesium orthosilicate ceramic, on the other hand, possessed much higher fracture toughness and has recently been reported in the literature as a suitable biomaterial. However, limited studies have been conducted to investigate the combination of these two bioceramics, of which are crucial parameters needed to substantiate its suitability as a reliable nanocomposite material. Hence for the current research, the development of hydroxyapatite-magnesium orthosilicate composite with improved mechanical properties was investigated. The effects and implications of combining these two bioceramics were assessed in terms of linear shrinkage, phase stability, bulk density, Young’s modulus, Vickers hardness, fracture toughness and microstructural evolution. In the present research, the hydroxyapatite powder was successfully synthesized through a novel wet chemical method and the magnesium orthosilicate powder was produced via combination of ultrasonification and mechanical ball milling method. Then the hydroxyapatite powder was mixed with magnesium orthosilicate accordingly to the concentration from 10wt. % to 50wt. % using the ultrasonification and mechanical ball milling method. Green samples were pressureless sintered at temperatures ranging from 1000°C to 1300°C at heating rate of 10°C / minute with a holding time of 2 hours. A secondary phase known as whitlockite was found in all the hydroxyapatite-magnesium orthosilicate composites after sintering. In general, the ceramic composites exhibited low mechanical properties across all the composition investigated. However, a high fracture toughness of 2.5 MPam1/2 was recorded for hydroxyapatite containing 20wt. % magnesium orthosilicate addition which indicated the potential of this composite to be used for load bearing biomedical applications. Moreover, the SEM graphs also demonstrated that formed whitlockite composite tends to form porous agglomerates. Such microstructure of calcium hydroxyapatite is one of the most frequently used bioceramics for bone and dental tissues reconstruction and for adsorption of hazardous materials from waste water and nuclear waste disposal.